Culturing of Avian Embryos for Time-Lapse Imaging - Paul A. Rupp; Brenda J. Rongish; Andras Czirok; Charles D. Little (BioTechniques)
Monitoring morphogenetic processes, at high resolution over time, has been a long-standing goal of many developmental cell biologists. It is critical to image cells in their natural environment whenever possible; however, imaging many warm-blooded vertebrates, especially mammals, is problematic. At early stages of development, birds are ideal for imaging, since the avian body plan is very similar to that of mammals. We have devised a culturing technique that allows for the acquisition of high-resolution differential interference contrast and epifluorescence images of developing avian embryos in a 4-D (3-D + time) system. The resulting information, from intact embryos, is derived from an area encompassing several millimeters, at micrometer resolution for up to 30 h.